Penanggulangan Penambangan Emas Illegal - Alva Viere Niwele; Fioren Mataheru; Iqbal Taufik (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2022)
Introductioan: The background of this writing is based on the facts which show Regency of Buruh is one of the districts with very rampant illegal gold mining activities, especially those carried out by the community. This is inseparable from various factors that cause illegal gold mining activities, both social, legal and economic factors.Purposes of the Research: This paper aims to describe the efforts to control the illegal gold mining activities of Mount Botak in Labor District, both those carried out by licensed companies and the community carried out conventionally. Methods of the Research: The research method used is normative juridical. do not yet have a People's Mining Business Permit, and 25 units of soaking tubs using cyanide and mercury are still found around the riverbanks around Mount Botak. Results of the Research: Overlapping mining permits, the absence of synergy between law enforcement officers in handling criminal acts in the mining sector, there is still a lack of public awareness of the impact of traditional mining, polluted the environment due to the disposal of mercury and cyanide waste, as a result of From this pollution, some babies born have structural defects in the form of physical abnormalities and functional disabilities such as Down syndrome. These defects occur because while their mothers are pregnant they consume water that has been contaminated with mercury and cyanide waste.